Public Readiness Index Entering New Normal Period Amidst the Covid-19 Pandemic As Exposure Effect to Social Campaigns - Pudjiastuti, Wahyuni (JURNAL KOMUNIKASI INDONESIA, 2022)
Indonesian people will face daily activities that are no longer the same as conditions before the corona-19 virus pandemic, which is then termed as New Normal. This policy is communicated in the form of a social campaign. Policy implementation should be a solution to improve welfare. But often, support from the public is still lacking. Therefore, it is necessary to study the level of public readiness (public readiness index) in accepting a policy and the effectiveness of the social campaign that the government has carried out. The research aims to describe the public readiness index for implementing the new normal and the effectiveness of the government’s social campaign in a community of students whose social problems are relatively high in the Child-Friendly City of Depok. It is hoped that the results can provide an overview and consideration in improving policies, especially for reopening face-to-face schools. Research is quantitative with an associative method. Researchers surveyed data collec- tion. The research population is junior high school students in Depok. The sample selection was conducted by multistage random sampling in a classter method, thus SMP N 6 and SMP BCIS (Budi Cendekia Islamic School) were selected. Data analysis was carried out descriptively to provide an overview of the variables studied and use regression to see the effect of the exposure variable on respondents’ readiness. The hypothesis is that the public acceptance of school children towards the new normal in the Child-Friendly City of Depok is influenced by their exposure to the government’s social campaign. The results showed that the level of readiness of junior high school students in Depok to enter the new standard period was at the confirmation stage, which was 31.67%, and the stabilization stage was 30%. Research also shows that this readiness is significantly influenced by exposure to social campaigns through television, online, and interpersonal commu- nication; thus, the proposed hypothesis can be accepted.